Improved 30-Day Heart Failure Readmissions Following Implementation of an Advanced Cardiovascular Education (ACE) Academy. Issue 4 (3rd October 2022) - Oliver, Beth; Travis, Arlene; Hughes, Ellen; Condrat, Lindsay; Ullman, Jennifer; Cohen, Bevin; Cartwright, Frances
Abstract : Background: Heart failure readmissions are common, though some are preventable through evidence-based management. Local Problem: Despite outperforming national benchmarks for 30-day readmissions, compliance with an evidence-based institutional heart failure management pathway was inconsistent. The purpose of this project was to reduce 30-day heart failure readmission rates through an educational intervention and an electronic health record (EHR) redesign. Methods: The cardiac services nursing leadership team conducted an education and documentation needs assessment to identify knowledge gaps and practical barriers to effective utilization of evidence-based interventions for heart failure management. Interventions: This intervention included an Advanced Cardiovascular Education (ACE) Academy and an EHR workflow redesign for clinical and supportive nursing staff. Results: The 30-day heart failure readmission rates reduced immediately following the intervention, and rates continued to decrease over a 3-year follow-up. Conclusions: Even among hospitals outperforming national benchmarks, 30-day heart failure readmissions can be reduced and sustained with enhanced education and EHR redesign.